Building the musical pedagogy and its development in the sound creation group of USC - Cárdenas Serván, María Inmaculada (2013)
This article, through the personal presentation of the teacher and researcher Immaculada CárdenasServán presents the evolution and the state of affairs of Pedagogy of Music Creation, in bothuniversity students, and in preschoolers. Nearly three decades in the search for the best way toconvey the essence of music. Acquiring a new listener within contemporary art proposals soundand musical ideas of other cultures through an update of the teaching of music, adapting it to newtechnologies and new values of today’s society, now called Pedagogy of Musical Creation and thatrecently would start calling it more in line Pedagogy of Resounding Creation.